2014
DOI: 10.1136/vr.102686
|View full text |Cite
|
Sign up to set email alerts
|

Understanding antimicrobial use and prescribing behaviours by pig veterinary surgeons and farmers: a qualitative study

Abstract: Increasing awareness of bacterial antimicrobial resistance in human beings and veterinary medicine has raised concerns over the issue of overprescribing and the indiscriminate use of antimicrobials. Their use in food-producing animals is under scrutiny due to the perceived risk from the zoonotic transfer of resistant pathogens from animals to human beings. This study used focus groups to explore the drivers and motivators behind antimicrobial use and prescribing by veterinary surgeons and farmers in the pig in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
129
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(141 citation statements)
references
References 41 publications
8
129
2
2
Order By: Relevance
“…Therefore, antibiotic prescribing decisions of veterinarians should be after consideration of intrinsic and extrinsic factors (e.g. type of husbandry practice in food-producing animals) (De Bryine et al 2013;Coyne et al, 2014;Speksnijder et al, 2015;Coyne et al, 2016). Even more concerning is that majority of the respondents in this study choose new generation antibiotics (e.g., extended-spectrum antibiotics) as first line of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, antibiotic prescribing decisions of veterinarians should be after consideration of intrinsic and extrinsic factors (e.g. type of husbandry practice in food-producing animals) (De Bryine et al 2013;Coyne et al, 2014;Speksnijder et al, 2015;Coyne et al, 2016). Even more concerning is that majority of the respondents in this study choose new generation antibiotics (e.g., extended-spectrum antibiotics) as first line of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Interview topic guides and the online survey questionnaire were informed by a rapid literature review (Alarcon, 2013;BfR, 2015;Buller et al, 2015;Coyne et al, 2014;De Briyne et al, 2016;Dean et al, 2015;European Commission, 2005, 2010Fontané, 2015;Gibbons, 2013;Hughes, Hermans and Morgan, 2008;Jan et al, 2012;Laanen et al, 2014;Moreno, 2014;Schulze-Geisthövel et al, 2016;Speksnijder et al, 2014 andSwinkels, 2015;and Visschers et al, 2015).…”
Section: Approach and Methodologiesmentioning
confidence: 99%
“…Similarly to farmers, veterinarians showed little concerns that antibiotics use in farming creates AMR risks in humans (e.g, Buller et al, 2015), and some believed there is little scientific evidence of these risks (Coyne et al, 2014).…”
Section: Studies On Veterinariansmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the criteria for discontinuing repeated treatment of consecutive batches of pigs are not clear. A British focus group study documented that both farmers and veterinarians found it difficult to decide when to withdraw prophylactic treatments (Coyne et al 2014). A recent Danish study (Pedersen et al, 2015) found that 84% of the farmers used some clinical inspection criteria to determine when to initiate treatment, while antibacterials were used systematically on a fixed day post-weaning in 16% of the herds, suggesting a prophylactic application.…”
Section: Introductionmentioning
confidence: 99%